Lipid nanoparticles loaded with 7-ethyl-10-hydroxycamptothecin-phospholipid complex: in vitro and in vivo studies. (18th August 2015) - Liu, Huan; Lu, Hua; Liao, Longfei; Zhang, Xuanmiao; Gong, Tao; Zhang, Zhirong
Abstract: 7-Ethyl-10-hydroxy-camptothecin (SN38), the active metabolite of irinotecan (CPT-11), is an effective antineoplastic agent against many malignancies. Although it is 100-fold to 1000-fold more potent than CPT-11, the clinical utility of SN38 has been extremely restricted because of its poor solubility in any pharmaceutically acceptable solvents. The aim of this study was to develop SN38 nanoparticles (SN38-PC-LNs) using pharmaceutically acceptable excipients, and investigate the therapeutic efficacies in vitro and in vivo . SN38-phospholipid complex (SN38-PC) was prepared and loaded into lipid nanoparticles. The particle size was approximately 200 nm with a narrow size distribution. A high encapsulation efficiency of 88.11% ± 1.41% and drug loading of 9.55% ± 0.84% were achieved under the optimal condition. SN38-PC-LNs exhibited potent cytotoxic effects against a panel of human tumor cell lines (HT-29, HepG2, A549 and MCF-7). In vivo evaluation proved the enhanced antitumor efficacy of SN38-PC-LNs in mice bearing S180 tumor as well. The results from this study demonstrated an effective formulation of SN38 has been developed, which is promising for the delivery of SN38 for tumor chemotherapy.